Social Communication in Dance Art and The Creative Industry - Emri, Emri; Loravianti, Susasrita; Minawati, Rosta; Sahrul, Sahrul (LPPM Institut Seni Indonesia Padangpanjang, 2023)
Social communication in the world of dance is an essential element in societal life. It not only facilitates the exchange of information and ideas but also builds and maintains social relationships within the arts. However, to ensure effective communication, it is necessary to address various challenges such as communication gaps and message distortion. A better understanding of social communication can help individuals and communities interact more effectively and harmoniously. Dance communication is an effective and powerful way to convey complex messages, emotions, and ideas. Through various mediums, artists can interact with their audience and build deep understanding and appreciation. However, to achieve effective communication, challenges such as diverse interpretations and cultural gaps must be addressed. Thus, art can continue to play a vital role as a communication tool in society. The creative industry is an economic sector focused on the creation and exploitation of intellectual and artistic works. It is a dynamic and rapidly growing sector that plays a significant role in the modern economy. By harnessing creativity and intellectual skills, this industry not only generates substantial economic value but also makes a significant contribution to cultural identity and innovation. However, to reach its full potential, various challenges such as intellectual property rights protection, funding, market access, and education need to be addressed. With appropriate support, the creative industry can continue to grow and provide greater benefits to society and the economy, especially in the field of dance arts